أثر المخاطر المنتظمة على الأداء المالي للبنوك التجارية الأردنية - صلاح، أحمد عبدالله محمد أحمد; الحموري، باسم محمد نزال (جامعة عمان العربية - عمادة البحث العلمي والدراسات العليا, 2020)
هدفت هذه الدراسة إلى بيان أثر المخاطر المنتظمة على الأداء المالي للبنوك التجارية المدرجة في سوق عمان المالي للفترة الممتدة من (1995-2017)، وانتهجت هذه الدراسة الأسلوب الإحصائي الوصفي التحليلي، كما تم استخدام Panel data لاختبار فرضيات الدراسة؛ ولتحقيق أهداف هذه الدراسة تم اختيار المخاطر الآتية (معدل التضخم، مخاطر سعر الصرف بعملتي اليورو والجنيه الإسترليني، مخاطر سعر الفائدة)، كما تم استخدام المؤشرات الآتية للتعبير عن الأداء المالي (العائد على الأصول، العائد على حقوق الملكية) واستخرجت البيانات من خلال البحث في التقارير المالية السنوية للبنوك التجارية قيد الدراسة ومن التقارير السنوية للبنك المركزي الأردني، حيث اشتملت عينة الدراسة على جميع البنوك التجارية المدرجة في سوق عمان المالي وعددها 13 بنكا. فقد توصلت هذه الدراسة إلى العديد من النتائج من أهمها وجود أثر ذو دلالة إحصائية عند مستوى الدلالة (0.05=α) للمخاطر المنتظمة (معدل التضخم، مخاطر سعر الصرف بعملة الجنيه الإسترليني، مخاطر سعر الفائدة) على الأداء المالي للبنوك التجارية، أما مخاطر سعر الصرف بعملة اليورو فقد توصلت إلى عدم وجود أثر ذو دلالة إحصائية عند مستوى الدلالة (0.05=α). في ضوء هذه النتائج أوصى الباحث بمجموعة من التوصيات من أهمها ضرورة القيام بمزيد من الدراسات لتحديد العوامل المؤثرة على الأداء المالي للبنوك المدرجة في بورصة عمان للأوراق المالية، كما أوصت الدراسة بضرورة اتباع آليات حديثة لتعامل مع التذبذب في أسعار صرف العملات والمخاطر المحيطة بها.
This study aims to show the regular effect on the Financial Performance of Commercial Banks listed in Amman Stock Exchange Market for the period from (1995-2017), this study followed the statistical descriptive analytical method, also Panel data was used to choose study hypotheses. To achieve this study, the following risks were selected (Inflation rate, the risks of exchange rate in the two currencies the Euro and the Sterling Pound and the interest rate risks). The following indicators were used to express financial performance (the revenue of assets, the revenue of the property rights). Data were extracted from the annual financial reports of the commercial banks under study and from the annual reports of the Central Bank of Jordan, where the study sample on all the commercial banks listed on the Amman Stock Exchange market and they are 13 banks. This study have reached to many results, and the most important one is the existence of the effect of statistical significance at the level of significance (50.0=α) for the regular risks (Inflation rate , the risks of exchange rate in the two currencies the Euro and the Sterling Pound and the interest rate risks) on the financial performance of the commercial banks however, for the exchange rate risk in the Euro currency, it is found that there was no statistically significance effect at the level of significance. (50.0= α). In the light of these results, the researcher recommended a number of recommendations, most importantly is doing further studies to determine the affecting factors on the financial performance of listed banks in Amman Stock Exchange Market for the financial securities. Also the study recommended on the necessity of following modern mechanisms to deal with the fluctuation in currencies exchange rates and the related risks.
Keywords: الخدمات المصرفية -- البنوك التجارية -- الأداء المالي -- إدارة المخاطر